Genomic Analysis Provides Insights Into the Plant Architecture Variations in in situ Conserved Chinese Wild Rice (Oryza rufipogon Griff.) - Yang, Ziyi; Zhang, Yilin; Xing, Meng; Wang, Xiaowen; Xu, Zhijian; Huang, Jingfen; Wang, Yanyan; Li, Fei; Nie, Yamin; Ge, Jinyue; Lou, Danjing; Liu, Ziran; et al. (Frontiers in Plant Science, 2022)
In situ conserved wild rice (Oryza rufipogon Griff.) is a promising source of alleles for improving rice production worldwide. In this study, we conducted a genomic analysis of an in situ conserved wild rice population (Guiping wild rice) growing at the center of wild rice genetic diversity in South China. Differences in the plant architecture in this population were investigated. An analysis using molecular markers revealed the substantial genetic diversity in this population, which was divided into subgroups according to the plant architecture. After resequencing representative individuals, the Guiping wild rice population was compared with other O. rufipogon and Oryza sativa populations. The results indicated that this in situ conserved wild rice population has a unique genetic structure, with genes that were introgressed from aromatic and O. sativa ssp. indica and japonica populations. The QTLs associated with plant architecture in this population were detected via a pair-wise comparison analysis of the sequencing data for multiple DNA pools. The results suggested that a heading date-related gene (DHD1) might be associated with variations in plant architecture and may have originated in cultivated rice. Our findings provide researchers with useful insights for future genomic analyses of in situ conserved wild rice populations.